Optimizing Healthcare Efficiency To Focusing On Patient Appointment Management - Naif Dhidan AlShammari , Khalid Abdullah AlBedaiwey , Mansour Bakheet AlOtaibi , Marzouq Haief AlOtaibi , Musaad Shujaa Al Harbi (Migration Letters, 2021)
Healthcare delivery relies heavily on effective appointment scheduling, which guarantees timely access to services and maximizes resource use. With an emphasis on increasing efficiency and delivering patient-targeted treatment more effectively, this quantitative analysis looks into factors impacting appointment management practices, impacted person studies, and healthcare outcomes. Records from healthcare records were analysed using logistic regression, ANOVA, risk stratification modelling, and Pearson correlational analyses to identify factors influencing appointment wait times, correlates between wait times and impacted person satisfaction ratings, and predictors of appointment non-compliance. The findings showed that appointment non-compliance was widely correlated with the kind of appointmen[1]t, the scheduling technique, and the demographics of the affected individuals. While younger age was associated with a higher likelihood of non-compliance, urgent appointments and online booking were linked to lower non-compliance rates. The examination of appointment waits times revealed significant differences, mostly linked to the kind of appointment and the scheduling strategy used; lower wait times were associated with online scheduling and urgent appointments. Furthermore, there was a weak link found between wait durations and affected person pride ratings, highlighting the negative effects of long wait times on affected person reports. The identification of high-chance patients for targeted actions to increase appointment adherence was made possible by the advancement of a danger stratification version. To maximize appointment management techniques, recommendations include investing in virtual health infrastructure, automating appointment procedures, and putting virtual scheduling systems into place. Healthcare organizations may improve patient experiences, improve healthcare delivery outcomes, and support fair access to treatment by addressing these suggestions.